Process improvement proposal for the reduction of machine setup time in a copper transformation company using lean manufacturing tools - Lora-Soto, Anthony (2021)
This study aimed to identify the causes of significant problems existing in the metallurgical sector, and a solution is proposed for the setup process. We detail the theoretical background of the processes in the lean manufacturing methodology, which will be applied to a rolling machine. Further, we provide a brief description of the company and the sector’s problems. We describe success stories of companies that implemented various lean manufacturing tools. We also present some of the results achieved across sectors to gain an in-depth understanding of the technique and a practical support of the implemented model. Our proposal is based on the lean manufacturing methodology; tools such as Single Minute Exchanges of Dies, Kaizen, 5S, and value stream mapping (VSM) will be used to reduce setup times and to impact machine layout and productivity positively. We also show the implementation results of a pilot plan conducted in the company over a period of more than 3 months.